2013
DOI: 10.2112/si65-361.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relation between sea level rise and shoreline erosion using sea level reconstructions: an example in French Polynesia

Abstract: In : International Coastal Symposium (ICS) : 2013 Proceedings (Plymouth, England )International audienceThe climate component of sea level variation displays significant spatial variability, and it is now possible to reconstruct how sea level varied globally and regionally over the past half century. The fact that sea level rose faster than the global mean since 1950 in the central Pacific stimulated a study of decadal shoreline changes in this region. Here, the study of Yates et al. (2013) was extended to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…For example, the respective contributions of seasonal swell and tropical cyclones were found to vary significantly between French Polynesian atolls. Le Cozannet et al () noted that changes were predominantly influenced by tropical cyclones on Tupai, while they were mainly controlled by the combined effects of tropical cyclones and trade wind swell on Tetiaroa. Additionally, Yates et al () and Le Cozannet et al () found that a given driver, for example, tropical cyclones, had opposite effects on nearby atolls and islands.…”
Section: Attribution Of Changementioning
confidence: 99%
“…For example, the respective contributions of seasonal swell and tropical cyclones were found to vary significantly between French Polynesian atolls. Le Cozannet et al () noted that changes were predominantly influenced by tropical cyclones on Tupai, while they were mainly controlled by the combined effects of tropical cyclones and trade wind swell on Tetiaroa. Additionally, Yates et al () and Le Cozannet et al () found that a given driver, for example, tropical cyclones, had opposite effects on nearby atolls and islands.…”
Section: Attribution Of Changementioning
confidence: 99%
“…In several sites, a relation between shoreline or beach changes, and rates of relative sea level rise has been found, e.g., along the eastern coast of the USA [ Zhang et al, ; Gutierrez et al, ], at beaches of two islands of Hawaii [ Romine et al, ], and in two deltas of Papua New Guinea [ Shearman et al ., ] and in Europe [ Yates and Le Cozannet , ]. Other studies have provided evidence that even in areas affected by fast sea level rise (e.g., western tropical Pacific) [ Becker et al ., ], the effects of sea level rise cannot be detected so far because they are masked by the effects of waves, currents, cyclones, and anthropogenic forcing agents [e.g., Le Cozannet et al ., ; Yates et al ., ]. Finally, in areas where sea level rise is close to the global average, there is evidence that other processes account for shoreline changes: natural factors such as the effects of waves and storms [e.g., Webb and Kench , ; Ford , ] or factors directly due to human actions such as coastal land reclamation or embankments [ Webb and Kench , ]. Moreover, even in areas not directly affected by human activities, indirect anthropogenic actions may impact the shorelines.…”
Section: Coastal Impacts Of Sea Level Risementioning
confidence: 99%
“…This disagreement between shoreline evolution and sea level fluctuation has been indicated by other authors (e.g., Clarke and Eliot, 1983;Lacey and Peck, 1998;Le Cozannet et al, 2013), who have noticed that shoreline erosion and accumulation processes on a decadal time scale do not coincide with the sea level rise. It was found that the slight trend in sea level rise (1.8 mm/yr) will not have a significant impact on the shoreline for at least 30-50 years (Pye and Blott, 2006), yet would produce an impact if sea level rise exceeded a certain threshold (Hoffmann and Lampe, 2007).…”
Section: Discussionmentioning
confidence: 79%